Activity of Sub‐Band Gap States in Ferroelectric Pb(Zr0.2Ti0.8)O3 Thin Films. (13th February 2020) - Ramakrishnegowda, Niranjan; Yun, Yeseul; Knoche, David S.; Mühlenbein, Lutz; Li, Xinye; Bhatnagar, Akash
Abstract: Defect or intermediate states within the band gap of ferroelectric oxides are known to impact functional characteristics such as saturated polarization. However, depending upon their respective position, such levels can also induce a substantial photoelectrical response under appropriate illumination and severely impact the conduction mechanism of an otherwise highly insulating material system. Sub‐band‐gap illumination is used to highlight the activity of these levels in epitaxially grown and ferroelectric Pb(Zr0.2 Ti0.8 )O3 thin films. Large transient effects are observed in relation to ferroelectric polarization and conductivity after illumination. In the case of polarization, light induces a "leaky" character, which eventually decays over a period of nearly 1.5 h. In conjunction, persistent photoconductivity is observed as the enhanced conductivity attained under illumination gradually decays over several minutes after removal of illumination. Thermally stimulated currents are measured to probe the presence of sub‐band gap states and analyze their effect over a wide range of temperature. The trapping nature of the states and their role in the conduction is found to be the underlying origin. Abstract : Direct proof of the impact of sub‐band gap states on the polarization and electrical properties of ferroelectric Pb(Zr0.2 Ti0.8 )O3 thin films is presented. Light induces a drastic increment in leakage current which fades away with time, and persistent photoconductivity which gradually decays over several minutes. Thermally stimulated current are measured to analyze the contribution of such states.